2016
DOI: 10.1080/21655979.2016.1197026
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus removal performance and population structure of phosphorus-accumulating organisms in HA-A/A-MCO sludge reduction process

Abstract: We developed a new sludge reduction HA-A/A-MCO (Hydrolysis-Acidogenosis-Anaerobic/Anoxic -Multistep Continuous Oxic tank) process, which has improved phosphate (P) and nitrogen (N) removal. Its biological treatment unit uses an A/O P & N removal process with hydrolysis acidification, multistep continuous aeration, and continuous flow, coupled with sidestream P removal by draining out anaerobic P-bearing wastewater. The process has advanced synchronization of P and N removal and sludge reduction. The improved p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the bottom spongy filling without casings (column B) there were 2.6 times more reads for Devosia. Zuo et al [ 52 ] showed that Devosia sp. and Bdellovibrio sp.…”
Section: Resultsmentioning
confidence: 99%
“…In the bottom spongy filling without casings (column B) there were 2.6 times more reads for Devosia. Zuo et al [ 52 ] showed that Devosia sp. and Bdellovibrio sp.…”
Section: Resultsmentioning
confidence: 99%
“…Phytoremediation-based techniques have indeed been effectively employed to degrade textile industry wastewater. Especially compared to other approaches, biological treatment (i.e., bioremediation) is cost-effective, environmentally beneficial, and creates less sludge [ 79 ]. It results in the oxidation of reactive polymers to a less hazardous inorganic product (i.e., chromophoric group) which ultimately aids in eliminating toxic compounds [ 80 ].…”
Section: Biological Methodsmentioning
confidence: 99%
“…Those publications indicate the possibility of providing a low-waste method consistent with the circular economy approach. The potential of combining removal methods was also demonstrated in the article by Zuo et al (2016), where the possibility of using the HA-A/A-MCO (Hydrolysis-Acidogenosis-Anaerobic/Anoxic-Multiple Continuous Oxic Tank) process was evaluated with removal of up to 95.2% P [ 185 ]. As in the case of the other methods, the utilization of adsorbents for the recovery of P can be the optimal solution in terms of reducing energy costs.…”
Section: Guidelines For a Practical Approachmentioning
confidence: 99%